2016
DOI: 10.1007/s40596-016-0490-6
|View full text |Cite
|
Sign up to set email alerts
|

What is Taught on Firearm Safety in Undergraduate, Graduate, and Continuing Medical Education? A Review of Educational Programs

Abstract: These results underscore a priority for developing firearm safety education programs in undergraduate, graduate, and continuing medical education settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Fulfilling this imperative requires the cultural competence and nuance necessary to have dedicated and respectful conversations with patients [13]. While low rates of gun safety counseling and lack of physician training to provide counseling are established [6,12,28,30,32], the present research is the first to illuminate the potent role that CME may play in increasing counseling. CME was strongly associated with providing firearm counseling often or very often, including asking patients with depression about their firearm access as well as increased knowledge of how to counsel.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fulfilling this imperative requires the cultural competence and nuance necessary to have dedicated and respectful conversations with patients [13]. While low rates of gun safety counseling and lack of physician training to provide counseling are established [6,12,28,30,32], the present research is the first to illuminate the potent role that CME may play in increasing counseling. CME was strongly associated with providing firearm counseling often or very often, including asking patients with depression about their firearm access as well as increased knowledge of how to counsel.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are promising, as they suggest that the provision of firearm safety counseling need not be a partisan issue; instead, our findings provide an opportunity for physicians across party lines to sensibly unite behind the need to provide accurate and effective firearm counseling to patients, as has been done before with safety issues like domestic violence, seatbelts, biking helmets, and smoking cessation. Perhaps the disparity between belief and low CME attendance rate is not driven by a lack of interest or perceived benefit but by the paucity of available CME firearm safety opportunities [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review identified only 4 reports on the development and assessment of training for clinicians (88). Input from clinician and nonclinician firearm owners is important (51).…”
Section: Discussionmentioning
confidence: 99%